Jejunal atresia presenting with mesenteric cyst in a neonate: a case report - Pandey, A (BioMed Central, 2008)
Jejunoileal atresia is a congenital anomaly that is characterized clinically by bilious vomiting and abdominal distension. It has been associated with various congenital anomalies but its association with mesenteric cyst has only been reported sporadically. As this is a very rare entity, it is being reported with a brief review of literature.